2013
DOI: 10.1007/s10103-013-1463-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with an Er:YAG laser and fluoride on the prevention of dental enamel erosion

Abstract: The aim of this study was to evaluate the effect of the Er:YAG laser and its association with fluoride (1.23% acidulate phosphate fluoride gel) on the prevention of enamel erosion. Sixty specimens were obtained from bovine enamel (4 × 4 mm), which were ground flat, polished, and randomly divided into five groups according to the preventive treatments: control-fluoride application; L--Er:YAG laser; L+F--laser + fluoride; F+L--fluoride + laser; L/F--laser/fluoride simultaneously. Half of the enamel surface was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
3
13
0
2
Order By: Relevance
“…In other words, the tested measures could not prevent the erosive effect of Coca-Cola on enamel micro-hardness. This result was in line with that of dos Reis Derceli et al 40 They also showed that the Er:YAG laser irradiation, APF gel application or combination of both could not prevent enamel erosion caused by Coca-Cola. Rocha et al 25 indicated that the application of stannous fluoride gel alone or combined with CO 2 laser irradiation could not protect the primary teeth against the erosive action of hydrochloric acid.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In other words, the tested measures could not prevent the erosive effect of Coca-Cola on enamel micro-hardness. This result was in line with that of dos Reis Derceli et al 40 They also showed that the Er:YAG laser irradiation, APF gel application or combination of both could not prevent enamel erosion caused by Coca-Cola. Rocha et al 25 indicated that the application of stannous fluoride gel alone or combined with CO 2 laser irradiation could not protect the primary teeth against the erosive action of hydrochloric acid.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have assessed the efficacy of fluoride alone and in combination with other protective measures in the prevention of erosion. 3,24,[39][40][41][42] Laser irradiation alone or combined with fluoride application has also been suggested to increase enamel acid resistance, 31,43 and some studies demonstrated the positive efficacy of Er:YAG laser in increasing enamel resistance against acid attacks and dental caries. 30,31,44 Although both caries and erosion are caused by the demineralization of enamel, their main etiologic factors and mechanism of development are totally different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies performed by Altinok et al (2011) [21] and Dos Reis Derceli et al (2013) [22] evaluated the use of Er:YAG laser to control the eroded enamel demineralization by means of in vitro analysis. In situ studies can lead lower lesions in erosion progression by accumulation of acquired pellicle by means of saliva, which is considered a protective factor [23].…”
Section: Introductionmentioning
confidence: 99%
“…53 In addition to the results described, another study applied irradiation with the same prefocused irradiation mode (4 mm distance), without water irrigation, with 60 mJ and 2Hz, and showed no beneficial results. 54 At 8 and 16 mm distances, tissue loss areas were observed. 53 These groups presented the same distance from the focus point, thus producing similar results on the irradiated enamel.…”
Section: Discussionmentioning
confidence: 95%